Exercise-based cardiac rehabilitation programs in the era of COVID-19: a critical review - Stefanakis, Marios; Batalik, Ladislav; Papathanasiou, Jannis; Dipla, Lefkothea; Antoniou, Varsamo; Pepera, Garyfallia (Reviews in cardiovascular medicine, 2021)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. Increased rates of morbidity and mortality have led to the increased need for the implementation of secondary prevention interventions. Exercise-based cardiac rehabilitation (CR) represents a multifactorial intervention, including elements of physical exercise and activity, education regarding healthy lifestyle habits (smoking cessation, nutritional habits), to improve the physical capacity and psychological status of cardiac patients. However, participation rates in CR programs remain low due to socioeconomic, geographical and personal barriers. Recently the COVID-19 pandemic restrictions have added another barrier to CR programs. Therefore there is an emerging need to further improve the types and methods of implementing CR. Cardiac telerehabilitation, integrating advanced technology for both monitoring and communicating with the cardiac population, appears to be an innovative CR alternative that can overcome some of the barriers preventing CR participation. This review paper aims to describe the background and core components of center-based CR and cardiac telerehabilitation, and discuss their implications for present day clinical practice and their future perspectives.
Keywords: Cardiovascular diseases; kardiovaskulární rehabilitace; Telerehabilitation; Cardiac rehabilitation; Pandemics; lidé; Cardiac Rehabilitation; telerehabilitace; Exercise training; pandemie; Humans; Secondary prevention; COVID-19 pandemic; COVID-19; SARS-CoV-2